CHO cells engineered for fluorescence read out of cell cycle and growth rate in real time. (28th May 2017) - Fuge, Grischa; Hong, Yaeseong; Riecken, Kristoffer; Zeng, An‐Ping; Jandt, Uwe
Abstract : For efficient production of recombinant proteins by mammalian cells in a bioreactor, optimal growth rates are required and represent the most important process parameter. We present the first successful attempt to monitor the growth behavior and cell cycle state of a mammalian production relevant cell line under bioreactor cultivation conditions up to 1.2 l, utilizing a fluorescent read‐out without the need of additional staining or marking. For this purpose, we developed two new production relevant cell line derivatives ( CHO‐K1 FUCCI CM & CHO‐K1 FUCCI CN ) and corresponding analytical methods. The approach is easily scalable, applicable to mammalian recombinant protein production cell lines, and it allows for real‐time monitoring using appropriate fluorescence probes. It is based on the Ubiquitination‐based Cell Cycle Indicator ( FUCCI ) system developed by Miyawaki et al. CHO‐K1 was chosen as a model cell line due to its close relationship to several production cell lines. 1 We defined a new process parameter i red, a quantitative and numerically robust representation of the cell cycle distribution, and demonstrate it to be linearly correlated with the cell cycle state and inversely related to the real time growth rate. Detection of growth rate limitations is possible earlier than using cell‐count‐based approaches. Analytics were compatible with bulk fluorescence methods, using a plate reader as well as a flow cytometer. For future real time applications in industry scale bioreactors we recommend the use of on‐line or at‐line fluorescence probes. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1408–1417, 2017